Ritual plants used by the Manobo tribe of Surigao del Sur, Philippines (Asian Journal of Ethnobiology, 2020)
Abstract. Jamera JKAM, Manting MME, Dapar MLG. 2020. Ritual plants used by the Manobo tribe of Surigao del Sur, Philippines. Asian J Ethnobiol 3: 41-50. Manobo tribe is culturally rich in traditional practices, medicinal uses, diversity, and traditional knowledge based on their community plant resources. They dwell in hinterlands and mountainous regions in the southern part of the Philippines and live an intricate life dependent on agriculture and forest plants. Traditional ecological knowledge and beliefs of indigenous peoples play an essential role in biodiversity conservation. This study seeks to investigate the use of ritual plants of the Manobo tribe in Hinapuyan, Carmen and Cabangahan, Cantilan, Surigao del Sur, and to identify the availability of ritual plants being used. Plant information with the local name, plant parts used, methods of preparation, ritual uses, and the Cultural Importance Index (CI) were quantified. This study documented a total of 12 traditional rituals associated with ritual plants. The five identified plant species are used in tribal rituals belonging to four different families: Arecaceae, Piperaceae, Poaceae, and Solanaceae. Arecaceae includes two species, while one species represents each of the families. Ritual plants with the highest CI were Areca catechu L., Piper betle L., and Nicotiana tabacum L. Manobo ritual plants have a symbolic meaning and rational function. This study is the first documentation of ritual plants presenting traditional ecological knowledge and cultural beliefs that must be saved to maintain biological diversity. The tribe cultivated some ritual plants and their wild plant collection in the village yard. These ritual plants are conserved and protected by the Manobo community. More investigations are recommended on the ritual plants used among diverse ethnolinguistic groups in the Philippines and other countries.
Keywords: Beliefs and practices, cultural importance index, ethnobotany, Manobo, ritual plants